Effectiveness of a communication skills training program for medical students to identify patients communicative clues. Issue 11 (November 2020) - Moral, Roger Ruiz; Andrade-Rosa, Cristina; Martín, Juan D Molina; Barba, Emilio Cervera; de Torres, Luis Pérula; Martín, Diana Monge
Highlights: Medical students receiving experiential training in Communication detected more communicative clues than those did not receive it. Following communicative clues allowed medical students to explore the patient's perspective. For medical students some communicative clues are more elusive than others. Abstract: Objective: This study explores whether an Experiential Training Programme (ETP) in communication skills (CS) improves students' ability to identify patients clues compared to those who follow a non-experiential training throughout their medical studies. Method: Intervention Group (IG): 85 4th-year medical students who received the ETP and Control Group (CG): 67 recently graduated students who did not receive it. Their immediate (written) response was requested to three expressions offered by patients containing communicative clues. The answers were grouped into 2 categories: Clue recognised and response patient-centred and the opposite. Three researchers analysed the answers. Results: Responses 366 (65 from the CG and 77 from the IG): 280 did not recognise clues: 131 (62%) in IG and 149 (96%) in CG and 86 recognised them: 80 (37.9%) in IG and 6 (3.9%) in CG (p = 0.000). Some clues were more elusive than others (p = 0, 003). Conclusions: The students who received the ETP in CS showed greater ability to explore patients perspective taking advantage of different types of communicative clues than those who did not receive it in a non-relational context. Practice implications: Further research is needed to assess whether this ability is maintained in simulated or real clinical situations.